Pengaruh Pertumbuhan Ekonomi dan Investasi terhadap Kesejahteraan Masyarakat Provinsi Kalimantan Selatan melalui Tingkat Partisipasi Angkatan Kerja - Masraniansyah, M.; Muzdalifah, Muzdalifah (PPJP ULM, 2024)
This study aims to determine (1) the direct effect of economic growth and investment on TPAK partially (2) the direct effect of economic growth, investment and TPAK on community welfare partially (3) the indirect effect of economic growth and investment on community welfare through TPAK as a whole. partial (4) the effect of economic growth and investment on TPAK simultaneously (5) the effect of economic growth and investment on people's welfare through TPAK simultaneously. This study uses time series data for 2010-2021 through a quantitative approach using the path analysis method. This study shows that economic growth has no significant effect on TPAK, while investment has a significant effect on TPAK. Economic growth, investment and TPAK have no significant effect on people's welfare. On the other hand, economic growth has a more indirect effect on people's welfare through TPAK, while investment has a more direct effect on people's welfare.